Respiratory syncytial virus associated hospitalizations in children with congenital diaphragmatic hernia - Bernhard Resch; Krisztina Liziczai; Friedrich Reiterer; Thomas Freidl; Michaela Haim; Berndt Urlesberger (Elsevier, 2018)
Background: To evaluate the risk of RSV infection in infants and children with congenital diaphragmatic hernia (CDH) over two consecutive RSV seasons. Methods: Retrospective, single-center cohort study from southern Austria including infants with CDH born between 1993 and 2012. Infants were retrieved by searching via ICD-10 codes Q79.0 and Q79.1 and by using a local electronic database. Children were followed over 2 years of life including at least two consecutive RSV seasons (November to April). We also defined a group of hypothetical RSV infections with the following criteria: 70% of the admissions due to a respiratory infection (diagnosis of bronchiolitis and/or LRI score ≥3) during the RSV seasons over the first 2 years of life, when no test for RSV was performed. Results: Twenty-nine of 45 infants with CDH comprised the study population (6 were lost to follow-up and 10 died) of whom 9 (31%) exhibited 17 hospitalizations due to respiratory illness. Two hospitalized infants (6.9% of the study population) tested RSV positive, one during the first and the other during the second RSV season. Nine of 29 infants (31%) had documentation of palivizumab prophylaxis, none (0%) had proven RSV hospitalization compared to 1 of 20 (5%) without prophylaxis during the first RSV season (p = 0.256). Including the hypothetical cases, we calculated 0 of 9 (0%) in the palivizumab group and 4 of 20 (20%) in the group without prophylaxis (p = 0.079). Conclusions: We found a moderate rate of proven RSV hospitalizations in infants with CDH, and palivizumab prophylaxis led to a non-significant reduction of proven and hypothesized RSV hospitalizations. Key Words: respiratory syncytial virus, congenital diaphragmatic hernia, respiratory tract infection, hospitalization